2011
DOI: 10.1007/s00122-011-1623-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of resistance to septoria tritici blotch in the French winter wheat cultivars Balance and Apache

Abstract: The ascomycete Mycosphaerella graminicola is the causal agent of septoria tritici blotch (STB), one of the most destructive foliar diseases of bread and durum wheat globally, particularly in temperate humid areas. A screening of the French bread wheat cultivars Apache and Balance with 30 M. graminicola isolates revealed a pattern of resistant responses that suggested the presence of new genes for STB resistance. Quantitative trait loci (QTL) analysis of a doubled haploid (DH) population with five M. graminicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 69 publications
4
46
0
Order By: Relevance
“…Moreover, the frequency distribution for the 149 RILs was not consistent with a single gene model for STB resistance and was continuous and followed normal distributions. Our results support the polygenic and quantitative inheritance of resistance to STB 1988;Lynch and Walsh, 1998;Tabib Ghaffary et al, 2011b). The relative skeweness toward the resistant parent during both seasons (Figures 1a, 1b, and 1c) would imply that multiple genes with complementary additive effects but with partial dominance toward resistance are conferring resistance derived from 'Salim'.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, the frequency distribution for the 149 RILs was not consistent with a single gene model for STB resistance and was continuous and followed normal distributions. Our results support the polygenic and quantitative inheritance of resistance to STB 1988;Lynch and Walsh, 1998;Tabib Ghaffary et al, 2011b). The relative skeweness toward the resistant parent during both seasons (Figures 1a, 1b, and 1c) would imply that multiple genes with complementary additive effects but with partial dominance toward resistance are conferring resistance derived from 'Salim'.…”
Section: Discussionsupporting
confidence: 67%
“…The partial resistance is durable under field conditions and is expressed as a reduction in epidemic development (Chartrain et al, 2004). During the last decade 18 major resistance genes (Stb1-Stb18) to STB have been identified and mapped in the wheat genome (Arraiano et al, 2007;Goodwin, 2007;Chartrain et al, 2009;Tabib Ghaffary et al, 2011a;2011b). These developments have greatly improved the efficiency of marker-assisted selection in bread wheat.…”
Section: Introductionmentioning
confidence: 99%
“…The most closely linked locus to Stb11 was once more barc008. An additional Septoria tritici blotch seedling resistance gene on 1BS was reported by Tabib Ghaffary et al (2011) in the French cultivar 'Apache'. Stb11 is treated as an isolate-specific QTL due to a continuous distribution of disease scores in progeny plants after inoculation of the pathogen and was mapped as a seedling resistance gene specific to isolate IPO90012 from Mexico.…”
Section: Discussionmentioning
confidence: 97%
“…So far, 16 major genes (reviewed in Goodwin 2007Goodwin , 2012Tabib Ghaffary et al 2011, 2012 and numerous Quantitative Trait Loci (QTL) with smaller effects (Simon and Cordo 1988;Jlibene et al 1994;Simón et al 2004) have been identified and mapped in the wheat genome. However, tightly linked molecular markers have not been available until very recently, so relatively few resistance genes have been used in wheat breeding programs.…”
Section: Introductionmentioning
confidence: 99%